2011
DOI: 10.1007/s11224-011-9751-x
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and crystallographic data investigations of noncovalent S···O interactions

Abstract: Weak SÁÁÁO bonding, a specific noncovalent interaction, plays crucial roles in fields as diverse as molecular recognition, crystal engineering, and biological systems. This article presents an ab initio investigation of a series of dimeric complexes formed between formaldehyde and several sulfur-containing molecules as electron accepters. The bond-length change, interaction energy, topological property of the electron density, and charge transfer of these SÁÁÁO bonds have been systematically investigated. More… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
36
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 49 publications
(63 reference statements)
0
36
0
Order By: Relevance
“…Secondly, an orbital contribution that involved the oxygen or fluorine lone‐pairs by second‐order perturbation theory analysis, according to NBO calculations, was also performed. The calculated stabilizing energies reveal that the interactions between the two correctly directed lone pairs (n O 25 or n F ) and the σ* C−S orbitals in these noncovalent intramolecular interactions are weak and that this contribution increases slightly when the conjugated chain is extended further (see the Supporting Information, Table S1). For BTF 2 and compound 1 , the n F →σ* CS stabilizing interaction has the same magnitude as the n O →σ* CS interaction in BTOMe (about 2 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, an orbital contribution that involved the oxygen or fluorine lone‐pairs by second‐order perturbation theory analysis, according to NBO calculations, was also performed. The calculated stabilizing energies reveal that the interactions between the two correctly directed lone pairs (n O 25 or n F ) and the σ* C−S orbitals in these noncovalent intramolecular interactions are weak and that this contribution increases slightly when the conjugated chain is extended further (see the Supporting Information, Table S1). For BTF 2 and compound 1 , the n F →σ* CS stabilizing interaction has the same magnitude as the n O →σ* CS interaction in BTOMe (about 2 kcal mol −1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Since 2007, the occurrence of s-hole bonding by Group IV-VI atoms has increasingly been recognized. [40,66,89,90,112,[165][166][167][168][169][170][171][172] An important indication that the s-hole concept is applicable to Group VI atoms came through surveys of large numbers of divalent sulfide crystal structures. [150,151] It was found that sulfur close contacts followed a pattern very much like that of halogens, shown earlier as 4 and 5.…”
Section: S-hole Interactions Of Group Iv-vi Atomsmentioning
confidence: 99%
“…In the biological area, Junming et al surveyed the Protein Data Bank in May 2010 and found a large number of S···O close contacts that fit the criteria of s-hole interactions. [169] An interesting case involves thiazole and selenazole nucleosides, which have antitumor activity that depends upon conformation-determining S···O and Se···O intramolecular interactions. [153,175]…”
Section: Moleculementioning
confidence: 99%
“…Geometries were optimized at the ab initio MP2/aug-cc-pVDZ level which has been shown to be of high accuracy, especially for weak intermolecular interactions of the type of interest here [35,[47][48][49][50][51][52] where the data are in close accord with CCSD(T) values with larger basis sets [38,53,54] and in excellent agreement with experimental energetics [55] . Binding energies were computed as the difference in energy between the dimer, and the sum of the optimized energies of the isolated monomers, corrected for basis set superposition error by the counterpoise procedure [56] .…”
Section: Methodsmentioning
confidence: 97%
“…Subsequent crystal database analyses [30,31] confirmed this geometric preference within the context of both proteins and smaller molecules. Other groups [32][33][34][35] attributed the attraction, at least in part, to charge transfer from the nucleophilic atom's lone pair to the antibonding orbital of the C-S bond, although induction and dispersion can be important as well [36] . Very recent research in this laboratory [37][38][39][40][41] has amplified and generalized the concept of charge transfer from the lone pair of an atom on one molecule to a σ* antibonding orbital on its partner, to a range of atoms that include P and Cl.…”
Section: Introductionmentioning
confidence: 99%